BSA-Seq Discovery and Functional Analysis of Candidate Hessian Fly (Mayetiola destructor) Avirulence Genes - Navarro-Escalante, Lucio; Zhao, Chaoyang; Shukle, Richard; Stuart, Jeffrey (Frontiers in Plant Science, 2020)
The Hessian fly (HF, Mayetiola destructor) is a plant-galling parasite of wheat (Triticum spp.). Seven percent of its genome is composed of highly diversified signal-peptide-encoding genes that are transcribed in HF larval salivary glands. These observations suggest that they encode effector proteins that are injected into wheat cells to suppress basal wheat immunity and redirect wheat development towards gall formation. Genetic mapping has determined that mutations in four of these genes are associated with HF larval survival (virulence) on plants carrying four different resistance (R) genes. Here, this line of investigation was pursued further using bulked-segregant analysis combined with whole genome resequencing (BSA-seq). Virulence to wheat R genes H6, Hdic, and H5 was examined. Mutations associated with H6 virulence had been mapped previously. Therefore, we used H6 to test the capacity of BSA-seq to map virulence using a field-derived HF population. This was the first time a non-structured HF population had been used to map HF virulence. Hdic virulence had not been mapped previously. Using a structured laboratory population, BSA-seq associated Hdic virulence with mutations in two candidate effector-encoding genes. Using a laboratory population, H5 virulence was previously positioned in a region spanning the centromere of HF autosome 2. BSA-seq resolved H5 virulence to a 1.3 Mb fragment on the same chromosome but failed to identify candidate mutations. Map-based candidate effectors were then delivered to Nicotiana plant cells via the type III secretion system of Burkholderia glumae bacteria. These experiments demonstrated that the genes associated with virulence to wheat R genes H6 and H13 are capable of suppressing plant immunity. Results are consistent with the hypothesis that effector proteins underlie the ability of HFs to survive on wheat.